NONTRADITIONAL SUPPORT OF THE WEST PORTAL OF TUNNEL POVAZSKY CHLMEC - Jan Faltýnek (Acta Polytechnica CTU Proceedings)
The paper is focused on general description of support elements used on the Western Portal of the tunnel Považský Chlmec in Slovakia, near the City of Žilina. It presents basic aspects of the method of the shell structure. In this case the shell structure in combination with pile walls was used. You can also find here detailed description of geotechnical behaviour together with the setting up of the numerical model constructed in PLAXIS. Conclusions of important points from the entire paper including results evaluation you can find at the end of the paper.